Economic and social drivers of antibiotic dispensing practices among community pharmacies in Nepal. Issue 5 (4th March 2021) - Acharya, Yubraj; Nepal, Prajwol; Yang, Di; Karki, Kshitij; Bajracharya, Deepak; Prentis, Tyler; Davis, Susan L.; Kaljee, Linda
Abstract: Objective: To assess economic and social drivers of dispensing antibiotics without prescription by community pharmacies in Nepal. Method: A survey was conducted among 111 pharmacy owners and managers in five districts. Information on demographic and economic characteristics of the pharmacies (e.g. revenue and profits from antibiotics) and their inclination to sell antibiotics without a physician's prescription under various scenarios (e.g. diarrhoea in a child) was collected. Univariate analysis was conducted to assess the demographic and economic characteristics. Bivariate analysis was conducted to examine the relationship between dispensing antibiotics without prescription and economic and social factors. Results: Azithromycin and amoxicillin were the most commonly dispensed antibiotics. The proportions of pharmacies reporting that they would 'most likely' or 'likely' dispense antibiotics without prescription to adult patients ranged from 36.9% (sore throat) to 67.6% (cough). The proportions for paediatric patients ranged from 62.2% (sore throat) to 80.2% (cough or diarrhoea). There was no consistent relationship between the likelihood of dispensing antibiotics and revenues, profits or the number of patients. Instead, dispensing behaviour was influenced by the pressure from the patient; the respondents were more likely to dispense antibiotics when the patient specifically asked for 'an antibiotic' rather than for 'a medicine', and 68.5% respondents ranked 'customer satisfaction' as the most important factor motivating their work. Conclusions: In Nepal, inappropriate sale of antibiotics by community pharmacists is high, particularly for paediatric patients. Additional research is needed to establish key drivers of this behaviour and to help design effective approaches to reducing AMR.